2022
DOI: 10.1097/pas.0000000000001941
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical Approach to Genetic Subtyping of Anaplastic Large Cell Lymphoma

Abstract: Anaplastic large cell lymphoma (ALCL) can be classified genetically based on rearrangements (R) of the ALK, TP63, and/or DUSP22 genes. ALK-R defines a specific entity, ALK-positive ALCL, while DUSP22-R and TP63-R define subgroups of ALK-negative ALCLs with distinct clinicopathologic features. ALK-R and TP63-R produce oncogenic fusion proteins that can be detected by immunohistochemistry. ALK immunohistochemistry is an excellent surrogate for ALK-R and screening with p63 immunohistochemistry excludes TP63-R in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 33 publications
(131 reference statements)
0
7
0
Order By: Relevance
“…Regardless of the staining intensity, the results of LEF1 and GrB immunostaining were considered positive when more than 75% and 20% of the tumor cells were stained, respectively. 11 The result of CD30 immunostaining was considered positive when more than 75% of the tumor cells were stained according to the current diagnostic criteria for ALCL. 1 The results of other immunostainings were considered positive when more than 5% of the tumor cells were stained.…”
Section: Pathological Findingsmentioning
confidence: 99%
See 4 more Smart Citations
“…Regardless of the staining intensity, the results of LEF1 and GrB immunostaining were considered positive when more than 75% and 20% of the tumor cells were stained, respectively. 11 The result of CD30 immunostaining was considered positive when more than 75% of the tumor cells were stained according to the current diagnostic criteria for ALCL. 1 The results of other immunostainings were considered positive when more than 5% of the tumor cells were stained.…”
Section: Pathological Findingsmentioning
confidence: 99%
“…In DUSP22-rearranged ALCL, LEF1 tends to be expressed in >75% of the tumor cells, and cytotoxic markers are typically absent. 8,11 In a previous study, the IHC of LEF1 identified the presence of DUSP22-R with a sensitivity of 93.8% and specificity of 96.0%; however, only seven pcALCLs were included in the study, including one or two with DUSP22-R. 8 Therefore, whether LEF1 IHC is useful for screening DUSP22-rearranged pcALCLs remains unclear.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations